Probing structural changes during ductile fracture in metallic glasses via in situ straining inside a MeV transmission electron microscope. (November 2018) - Chang, H.J.; Kim, S.Y.; Moon, W.-J.; Kim, Y.-M.; Park, E.S.; Kim, D.H.
Abstract: Structural changes in the vicinity of a crack during ductile fracture in various metallic glasses (MGs) with the propensity of forming shear bands were investigated by in situ straining inside a MeV transmission electron microscope (TEM). During tensile loading, a plastic deformation zone with a width of ∼100 nm and shear bands with a width of ∼15 ± 5 nm developed from crack tips of ductile fracture in MGs. In particular, crack propagation by nanovoid formation and coalescence was observed in Ti40 Zr29 Cu9 Ni8 Be14  MG with the highest compressive plasticity (∼6.7 ± 0.5%) among the tested MGs, whereas this process was hardly observable in other MGs. This difference may be attributed to atomic scale heterogeneities in Ti40 Zr29 Cu9 Ni8 Be14  MG induced by icosahedral short range orders (ISRO), which cause pronounced shear band branching and thus delay fracture process. Meanwhile, no crystallization of MGs even with ISRO or with lower T x (crystallization onset temperature) was observed during in situ straining inside the MeV TEM and uniaxial tensile test with ribbon samples; a possible effect of normal stress and nanovoid formation during in situ straining is discussed to compare with crystallization during uniaxial compression test of the same MGs. Our study provides an insight into intrinsic toughening of MGs and thus can give useful guidelines on how to delay ductile fracture processes of MGs by tuning nanovoid formation, taking advantage of structural features through customized design of MGs. Graphical abstract: Highlights: Structural changes near crack during fracture in metallic glasses were investigated by in-situ straining in a MeV TEM. Plastic deformation zone (width=~100 nm) develops ahead of the crack tip, enveloping the shear bands. Crack winding by preferential formation and coalescence of nanovoids occurs in Ti-based metallic glass with ISRO. Under tensile loading, no crystallization occur due to lower critical shear fracture stress and less stress concentrations. Our study provide useful guideline on intrinsic toughening of metallic glasses, customizing the structural features.